Health insurance literacy among head and neck cancer patients and their caregivers: A cross‐sectional pilot study. Issue 6 (20th October 2022) - Nguyen, Oliver T.; McCormick, Rachael; Patel, Krupal; Reblin, Maija; Kim, Lindsay; Hume, Emma; Powers, Benjamin; Otto, Amy; Alishahi Tabriz, Amir; Islam, Jessica; Hong, Young‐Rock; Kirchhoff, Anne C.; et al.
Abstract: Objective: Health insurance literacy interventions may reduce financial burden and its effects on cancer patients and their caregivers. However, little is known about the health insurance literacy levels of head and neck cancer (HNC) patients and their caregivers. We assessed the feasibility of screening for health insurance literacy in a pilot study and described the health insurance literacy levels of HNC patients and their caregivers. Methods: We administered a survey that assessed demographics and subjective and objective health insurance literacy to HNC patients and their caregivers. Subjective health insurance literacy was measured through the Health Insurance Literacy Measure (score range: 0–84). Objective health insurance literacy was measured through correct answers to a previously developed 10‐question knowledge test. Due to a small sample size, inferential statistics were not used; we instead descriptively reported findings. Results: The pilot included 48 HNC patients and 13 caregivers. About 44.4% of patients and 30.8% of caregivers demonstrated low health insurance literacy (HILM ≤60). On the 10‐item knowledge test, patients had an average of 6.8 (SD: 2.3) correct responses and caregivers had 7.8 (SD: 1.1) correct responses. Calculating out‐of‐pocket costs for out‐of‐network services was challenging; only 9.5% of patients and 0% of caregivers answered correctly. Conclusion: Additional outreach strategies may be needed to supplement screening for health insurance literacy. Areas of focus for interventions include improving understanding of how to calculate financial responsibility for health care services and filing an appeal for health insurance claim denial. Level of Evidence: IV